Syhthesise [sic] a sustainable sago industry - Wan, Yoke Kin (2016)
Various sago biomass (i.e., sago barks, fibres and wastewater) that potentially converted into value-added products are generated during sago starch extraction process (SSEP). In current industrial practices, such biomass are disposed to the environment and caused severe environmental issues. Therefore, in order to minimise the environmental impacts and to improve economic performance of sago industry, sago biomass is vital to be recovered. On the other hand, a sustainable sago value chain, which involved activities plantation, harvesting, sago starch extraction process (SSEP), and transportations, is synthesised in this thesis via Fuzzy Multi-Footprint Optimisation (FMFO) approach. This proposed approach considered carbon, water, and workplace footprints as well as economic performance of sago value chain. In order to trade-off the conflicts among the optimisation objectives, the concept of fuzzy optimisation is adopted in this approach. Then, recovery of sago biomass in SSEP is focused. In order to prioritise sago biomass for recovery in sago industry, Material Flow Cost Accounting (MFCA)-based prioritisation approach is developed in this thesis. This MFCA-based approach introduced hidden cost (HC) and carry-forward cost (CFC) to determine cost associated with waste streams. Based on the associated cost, waste streams can be prioritised for recovery. Then, this MFCA-based prioritisation approach is further extended as extended MFCA (eMFCA)-based approach to simultaneous synthesise total resource conservation network (RCN) with industrial processes. In this thesis, total water network and SSEP is synthesised simultaneously via eMFCA-based approach. Furthermore, techno-economic and environmental performance of conversion of sago barks and fibres into combined heat and power (CHP) and bioethanol is evaluated. In addition, sensitivity analysis on payback period is conducted in different scenarios due to variation of feedstock cost, enzyme cost, and labour cost. In order to further improve sustainability of sago industry, a conceptual integrated sago-based biorefinery (SBB) is envisaged. Maali’s method is adopted in this thesis to allocate the benefits of each party participating in integrated SBB. Lastly, conclusions and future works are included in the end of this thesis.